The miracle planet - Brown, Bruce, 1950-; Morgan, Lane, 1949- (New York City : Gallery Books, 1990)
Provides an illustrated narrative of Earth's 4.6 billion-year history and the progress science is making in deciphering its mysteries.
"Based on the acclaimed PBS television series."--Jkt.
Includes bibliographical references (p. 242-249) and index.
Booklist.
Wilson's Public Library.
Adult.
Adult
Keywords: Geology; Earth; Earth